Self-regulatory-based compliance module improve chronic kidney failure patients condition - Melastuti, Erna; Nursalam, Nursalam; Priyantini, Diah (International Journal of Public Health Science (IJPHS), 2024)
Adherence is very important to pay attention to in health management and the quality of life among end-stage renal disease (ESRD) patients, in the fact that adherence is still lacking. This study aimed to analyze the effect of self-regulatory-based compliance modules improving interdialytic weight gains (IDWG), blood pressure (BP), sodium levels, and functional independence. A quantitative research design with a quasi-experiment approach (pre and post-test control study). A total of 28 samples for each group were taken using purposive sampling. Self-regulation based on health promotion was given using module and IDWG, sodium levels, BP measured with laboratories and physical examination, and Functional Independence measured using a questionnaire. Wilcoxon signed-rank test and Mann-Whitney test were the selected analyses for this study. There was a significant effect on self-regulation-based compliance to IDWG (p=0.012), sodium levels (p=0.001), systolic pressure (p=0.003), and functional independence (p=0.002) in the intervention group. A significant difference was also shown between the two groups (p<0.05). The self-regulation-based compliance module showed improved patient compliance in terms of fluid restriction, taking drugs, paying attention to diet, and managing activities. Adherence to patients increases good outcomes in controlling IDWG, BP, sodium levels, and functional independence in ESRD patients.